2017
DOI: 10.1051/matecconf/201710804005
|View full text |Cite
|
Sign up to set email alerts
|

Model and Simulation of Globoidal Cam Mechanisms with Oscillating and Dual Stopping Followers

Abstract: Abstract. Globoidal cam mechanisms with oscillating and dual stopping followers are necessary to accomplish the rise-dwell-fall-dwell periodic motion.The trajectory surface of roller axis of oscillating globoidal cam mechanism is the offset surface of working surface of the cam, and its mathematical model is relatively simple. According to the spatial geometric relationship, the coordinate equation of trajectory surface of roller axis is derived and the original angle positions for dual stopping followers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…studied the periodic motion of a rise-dwell-fall-dwell cam profile for a globoidal cam and a dual stopping followers. 9 Alzate et al. observed that the follower is detached from the cam under the variation of cam angular speed and showed an emergence periodic impacts and chattering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…studied the periodic motion of a rise-dwell-fall-dwell cam profile for a globoidal cam and a dual stopping followers. 9 Alzate et al. observed that the follower is detached from the cam under the variation of cam angular speed and showed an emergence periodic impacts and chattering.…”
Section: Introductionmentioning
confidence: 99%
“…8 Ge et al studied the periodic motion of a rise-dwellfall-dwell cam profile for a globoidal cam and a dual stopping followers. 9 Alzate et al observed that the follower is detached from the cam under the variation of cam angular speed and showed an emergence periodic impacts and chattering. 10 DasGupta and Ghosh used a constant pressure angle to assess jamming of the follower in its guide by taking into account the follower-guide friction.…”
Section: Introductionmentioning
confidence: 99%